2022
DOI: 10.1155/2022/2424011
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Anti-Infective Treatment of 9 Neonates with Raoultella ornithinolytica Sepsis

Abstract: Raoul ornithine-releasing bacteria widely exist in water, plants, and soil, and colonize the digestive tract and upper respiratory tract of the human body. They are aerobic, unpowered, and capsular opportunistic pathogens. The infectivity of this bacterium is still uncertain, but the possibility of nosocomial infection has been mentioned in the literature. Studies have pointed out that the bacterium should be diagnosed in time and sensitive antibiotics should be used early. Once complicated with sepsis, it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%